KESADARAN HUKUM PEREMPUAN BERPERAN GANDA PASCA PERCERAIAN (Studi Kasus Di Kecamatan Tanjung Raya Kabupaten Agam) - Yunita Eliza; Ikhwan . (Jurnal AL-AHKAM, 2020)
This research is intended as a study to find out the legal awareness of women's dual roles after divorce in assuming double responsibility. Obligation to provide income to children of ex-husband or father is an important issue as a form of responsibility of a father to the child, even though divorced. However, in reality, the decision to determine the cost of child care that has been determined by the Religious Court Judge and charged to ex-husband is not obeyed, so that mothers who look after children have difficulties in supporting their children and choose to take over the roles and obligations of ex-husband. This study aims to: First, find out how women's knowledge plays a dual role after divorce in Tanjung Raya District, Agam Regency. Second, knowing how women's understanding plays a dual role after divorce in Tanjung Raya District, Agam Regency. Third, find out how women's attitudes play a dual role in dual roles in households in Tanjung Raya District, Agam Regency. Fourth, knowing how women's behavior plays a dual role in assuming double responsibility in Tanjung Raya District, Agam Regency.This research is a field research with a qualitative approach. Qualitative research emphasizes the analysis of thought processes inductively related to the dynamics of the relationship between observed phenomena, and always using scientific logic. The technique of collecting data is done through observation and interviews. Interviews were conducted with 10 women who had divorced their husbands (widows) in Tanjung Raya Sub-District, Agam Regency. Testing the validity of the data is done by cross-checking between one interview result with another interview.This research shows that women's legal knowledge plays a dual role, namely some women know the provisions that their ex-husband still has obligations and some other women do not know the provisions. Understanding women's law plays a dual role tends not to understand the rule of law in detail. Women's legal attitudes play a dual role after divorce including attitudes to accept applicable provisions and attitudes of not expecting the entry into force of the law because they only focus on the roles they perform. Women's legal behavior plays a dual role after divorce and ex-husband is not in accordance with the rule of law and women play a dual role after divorce does not claim their rights to court.     Whereas women's legal awareness plays a dual role in Tanjung Raya District, Agam Regency is still low. This can be seen from several factors including the low level of education, lack of legal socialization, the influence of community culture, and the strengthening role of women in society